The need to work by educated Muslim women in Malaysia / Suhaida Mohd Amin and Mohd Faizal P.Rameli - Mohd Amin, Suhaida; P.Rameli, Mohd Faizal (2017)
Islam provides the opportunity for all Muslims, whether men or women in terms of employment and working opportunities. Hence, for those with higher educational attainment, knowledge and skills that they are acquired is expected could give positive return to the investment in human capital. Previous studies have suggested that there are many factors influenced women's participation in the labor market. However, there is a few difference reasons for working based on the level of education of the woman herself. To give the same value to adherence of religion, husbands or family and family-related responsibilities, this study focuses on the need to work among Muslim women. The scope of the study is focused on those with tertiary education to show their ability to earn a good career and salary. Thus, information from 746 educated Muslim women were collected via online survey. Respondent answers were analyzed using descriptive analysis and multiple responses to determine the extent of how educated Muslim women in Malaysia listed their need to work. The results showed that the need to work by educated Muslim women is to have their own sources of income, to help families financially, to pay debts and loans, to improve the standard of living, to practice what they have learned and to get self-satisfactory. Besides, this study also highlighted the differences in main reasons for working by different marital status. Finding of this study indirectly, demonstrates the importance of women's economic contribution to the family, especially to facing the current economic environment.